Advances in mild photothermal hydrogel-based therapies for bone and soft tissue injuries - Na, Peng; Jiang, Jing-Lun; Lv, Ren-Peng; Yang, Fan; Li, Shi-Feng; Chen, Xian-Zhuo (Frontiers in Cell and Developmental Biology, 2025)
Bone and soft tissue injuries resulting from trauma, metabolic disorders, and tumors pose a serious threat to public health, and their treatment faces numerous challenges, including infection, chronic inflammation, and impaired vascularization. Photothermal hydrogels, a new class of biomaterials, can sterilize tissues via photothermal therapy (PTT) and, through intelligent material design, exhibit multiple biological functions such as modulating the pathological microenvironment in bone and soft tissues. These properties have earned them a reputation as a “star material” in tissue engineering. However, excessive heating (above 50 °C) can cause irreversible thermal damage to tissues. Therefore, functional hydrogels that generate a mild photothermal effect (approximately 40 °C–45 °C) have recently become a research focus. This review provides a comprehensive overview of the types and fabrication strategies of photothermal agents used in mild photothermal hydrogels, systematically summarizes recent progress in their applications for bone and soft tissue injury repair, and delves into the underlying mechanisms by which they promote tissue regeneration. By summarizing current findings and outlining future perspectives on the use of mild photothermal hydrogels in modern regenerative medicine, we aim to advance the development of tissue engineering.